THE THREEFOLD PATH OF SPIRITUAL DEEPENING. - Deardorff, David (Epiphany International)
The article discusses the journey towards spiritual deepening. There are no fixed guidelines for seeking spiritual deepening as this journey is unique and personal for every individual. Spiritual deepening is particularly useful for those who are encountering mid-life crises. A reading program is suggested to help in discovering spiritual deepening.